Methicillin-Resistant Staphylococcus aureus Bloodstream Infections and Injection Drug Use, Tennessee, USA, 2015–2017 - Meghana P. Parikh; Rany Octaria; Marion A. Kainer (Emerging Infectious Diseases, 2020)
Recently, Tennessee, USA, has seen an increase in the use of commonly injected drugs, such as heroin and fentanyl. Injection drug use (IDU) practices can lead to life-threatening methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSIs) and other serious diseases. We matched MRSA BSIs identified through the National Healthcare Safety Network to the Tennessee Hospital Discharge Data System to characterize the prevalence, demographics, and clinical characteristics associated with IDU in this disease population. Of the 7,646 MRSA BSIs identified during 2015–2017, we found that 1,839 (24.1%) were IDU-related. IDU-related BSIs increased by 118.9%; the greatest rise occurred among emergency department–onset infections (197.4%). IDU was more often associated with white, female, 18–49-year-old, and uninsured persons (p<0.001). We found >1 additional IDU-related diagnoses in 84.2% of IDU-related BSIs. Targeted harm reduction strategies for persons at high risk of IDU are necessary to reduce MRSA BSIs in acute care settings.